2013
DOI: 10.1302/0301-620x.95b11.31633
|View full text |Cite|
|
Sign up to set email alerts
|

The outcome of total ankle replacement

Abstract: We performed a systematic review and meta-analysis of modern total ankle replacements (TARs) to determine the survivorship, outcome, complications, radiological findings and range of movement, in patients with end-stage osteoarthritis (OA) of the ankle who undergo this procedure. We used the methodology of the Cochrane Collaboration, which uses risk of bias profiling to assess the quality of papers in favour of a domain-based approach. Continuous outcome scores were pooled across studies using the generic inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
68
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(83 citation statements)
references
References 79 publications
(28 reference statements)
8
68
2
2
Order By: Relevance
“…Refinement of implant design by adoption of mobile bearings and technological advances has gradually improved the clinical outcomes after TAA. A recent systematic review of recent TAA studies, reported an overall survivorship of 89 % at 10 years [1]. Based on improved clinical outcomes, TAA has become increasingly popular as an alternative to arthrodesis, which has long been the gold standard for treating end-stage ankle arthritis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refinement of implant design by adoption of mobile bearings and technological advances has gradually improved the clinical outcomes after TAA. A recent systematic review of recent TAA studies, reported an overall survivorship of 89 % at 10 years [1]. Based on improved clinical outcomes, TAA has become increasingly popular as an alternative to arthrodesis, which has long been the gold standard for treating end-stage ankle arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Although TAA has been recently popularized worldwide, it is still accompanied by higher rates of complications compared with total hip and knee arthroplasties [1, 1315]. Surgeon understanding of the complications and their risk factors is important to provide good clinical outcomes; however, there is limited evidence available in the literature about risk factors for perioperative complications after TAA.…”
Section: Introductionmentioning
confidence: 99%
“…1 The National Institute for Healthcare and Clinical Excellence (NICE) risk assessment tool categorises TAR as a high-risk procedure for pulmonary embolism (PE), 2 but the true incidence of venous thromboembolism (VTE) following TAR is largely unknown, with several papers reporting a wide variation in incidence ranging from 0% to 4.8% (table 1). [3][4][5][6][7][8][9][10][11][12][13][14] These studies demonstrate ambiguity of definition of VTE; methodological flaws; and small single centre retrospective reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Newer prosthesis is uncemented, comprises two or three modular components, and has improved outcomes. A recent systematic review reported 89% survival of 7942 TARs at 10 years and an improvement in American Orthopaedic Foot and Ankle Society score (AOFAS) from 40 to 80 at a mean of 8.2 years of follow-up [22]. However, a further review from Gougoulias et al of 1105 total ankle arthroplasties reported a 10% failure rate at 5 years with residual pain in 27%–60% of cases [23].…”
Section: Introductionmentioning
confidence: 99%